1978
DOI: 10.1111/j.1095-8649.1978.tb03469.x
|View full text |Cite
|
Sign up to set email alerts
|

Observations on development and morphological effects of histamine liberator 48/80 on PAS‐positive granular leukocytes and heterophils of Catostomus commersoni

Abstract: Developmental stages of the two circulating blood granulocytes, the heterophil and the periodic acid-Schiff-positive granular leukocyte (PAS-GL) are described. There are no metachromatic basophils in this fish and eosinophils, when present, are confined to extravascular tissues. Fish were killed up to 24 h after injection with histamine liberator 48/80. Morphological (L/M and E/M) and histochemical studies of blood, haemopoietic tissue and gills from experimental fish were compared with those of untreated cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 15 publications
1
8
0
1
Order By: Relevance
“…This process is essentially identical to that reported for EGC of the trout intestine with release of granules being preceded by appearance of perigranular halos and a reticulated appearance of the granule contents [25,26]. The homogeneous appearance of these granules was similar to that reported for most fish EGC and some mammalian MC [14,15,26,27]. Complex ''crystalline'' or ''scroll'' sub-structures often reported in mammalian MC granules and occasionally in fish EGC were not observed in the damselfish.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…This process is essentially identical to that reported for EGC of the trout intestine with release of granules being preceded by appearance of perigranular halos and a reticulated appearance of the granule contents [25,26]. The homogeneous appearance of these granules was similar to that reported for most fish EGC and some mammalian MC [14,15,26,27]. Complex ''crystalline'' or ''scroll'' sub-structures often reported in mammalian MC granules and occasionally in fish EGC were not observed in the damselfish.…”
Section: Discussionsupporting
confidence: 63%
“…Exposure of EGC in the submucosa of the rainbow trout (Oncorhynchus mykiss) and the white sucker (Catostomus commersoni) to agents such as compound 48/80 was reported to result in significant decreases in the number of EGC observable with light microscopy, apparently due to a loss of sufficient granules to allow identification of these cells by light microscopy (as confirmed using electron microscopy) with a secondary loss due to emigration of EGC to other tissue regions [14,26,27]. In contrast, degranulating cells in the damselfish were readily observed and scored as such by light microscopy in both the gut and in tumors.…”
Section: Discussionmentioning
confidence: 93%
“…However, both PAS-GLs and basophils were present in the peripheral blood of N. ater in this study, and the concurrent presence of metachromatic basophils and PAS-GLs has been reported in other teleost species, such as S. lima (Bianchi et al 2014). This evidence suggests that PAS-GLs may not be the evolutionary precursor of basophils, as suggested by Barber and Westermann (1978b) ater were similar to those described in other Siluriformes such as I. punctatus (Williams and Warner 1976;Tavares-Dias and de Moraes 2007) and moustache catfish (Synodontis membranacea) (Owolabi 2011). Metachromatic staining of muccopoysaccharide granules in toluidine blue occurs in mammalian basophils (Cooper and Cruickshank 1966), and the use of 0.5% alkaline (pH 9) toluidine blue, as used in this study, has revealed metchromatic granules within basophils in several fish species (Tavares-Dias 2006b).…”
Section: Discussionmentioning
confidence: 63%
“…Since many of these histamine-induced morphological changes were similar to those observed in mammalian basophils and mast cells during histamine release, and basophils were absent in the peripheral blood of C. commersoni, it was suggested that PAS-GLs may be functionally equivalent to, or evolutionary precursors of, basophils or mast cells (Barber and Westermann 1978b;Tavares-Dias 2006a). However, both PAS-GLs and basophils were present in the peripheral blood of N. ater in this study, and the concurrent presence of metachromatic basophils and PAS-GLs has been reported in other teleost species, such as S. lima (Bianchi et al 2014).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation